LANGUAGE USED IN THE POSTERS OF LEGISLATIVE CAMPAIGN IN 2019 - Puji Laksono (Metaphor, 2019)
Posters played an important role in the legislative campaign in Wonosobo district 2019. Legislative candidates tried to influence voters by creating posters that contain interesting photos and writings. This is what encourage researcher to conduct research on the functions of languages ​​that exist in the poster. The researcher used qualitative research. Data were collected through observation. The result is that there are two types of language in the poster. The first is the language that gives information and the second is language that informs and influences voters to do something.